The metabolic vulnerability index as a novel tool for mortality risk stratification in a large-scale population-based cohort - Jialin Li; Qiuhong Man; Yingzhe Wang; Mei Cui; Jincheng Li; Kelin Xu; Zhenqiu Liu; Li Jin; Xingdong Chen; Chen Suo; Yanfeng Jiang (Redox Biology)
Metabolic malnutrition and inflammation—key mechanism links to redox imbalance—are fundamental pathologies that accelerate aging and disease progression, ultimately leading to death. The recently proposed metabolic vulnerability index (MVX) integrates multiple circulatory biomarkers closely linked to both metabolic and inflammatory factors. This study aims to assess MVX's potential to predict mortality in community-based population. In this large community-based prospective study, we included UK Biobank participants who underwent plasma metabolomics analysis. Gender-specific MVX scores were calculated based on six established biomarkers of mortality. Linear and non-linear associations between MVX and mortality were assessed using Cox proportional hazards models and restricted cubic spline models, respectively. Among the 274,092 UKB participants, 24,241 all-cause deaths occurred during a median follow-up period of 13.7 years. A significant, graded positive association was observed between MVX quartiles and all-cause mortality risk (P for trend <0.05), with the highest MVX quartile exhibiting the greatest risk (HR = 1.21 and 95 % CI = 1.16–1.25 after full adjustment). Females had higher MVX score than males (P < 0.05), but males with the same MVX score faced a greater mortality risk. Baseline age and comorbidities interacted (P for interaction <0.05 and synergy index >1) with MVX on mortality risk. Longitudinal analyses showed that females with persistently high MVX score had a significantly increased risk of mortality (HR = 1.39 in fully adjusted model). Collectively, these findings highlight MVX as a novel tool that captures metabolic and potential redox vulnerabilities in community residents, and serves as a valuable resource for identifying high-risk individuals of mortality. Further research is warranted to investigate the underlying mechanisms and establish causal relationships.